2019
DOI: 10.1002/ange.201904537
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulating Perovskite Quantum Dots in Iron‐Based Metal–Organic Frameworks (MOFs) for Efficient Photocatalytic CO2 Reduction

Abstract: Theauthors declare no conflict of interest.Keywords: CO 2 reduction ·i ron ·metalorganic frameworks (MOFs) ·perovskite quantum dots · photocatalysis Figure 3. a) Mott-Schottky plots of PCN-221(Fe 0.2 )and b) MAP-bI 3 @PCN-221(Fe 0.2 ). c) Steady-state photoluminescence spectrao f PCN-221, PCN-221(Fe 0.2 ), MAPbI 3 @PCN-221,a nd MAPbI 3 @PCN-221-(Fe 0.2 ). d) Time-resolved photoluminescence decays of PCN-221, PCN-221(Fe 0.2 ), MAPbI 3 @PCN-221, and MAPbI 3 @PCN-221(Fe 0.2 )with ET519LP as long-wavelength pass f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 62 publications
1
45
0
Order By: Relevance
“…To address these issues, metal-organic frameworks (MOFs), bene ting from their porous feature, ordered structure and molecular tunability, have been widely used to mediate photocatalytic CO 2 reduction. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In this eld, Lin et al, 16 incorporated Re(CO) 3 (bpy)Cl (bpy = bipyridine) modules into the UiO-67 framework, achieving a total turnover number (TON) of 10.9 in photocatalytic CO 2 -to-CO conversion. Wang et al achieved a high TON of 450 by using a Co-based zeolitic imidazolate framework as the cocatalyst in the presence of [Ru(bpy) 3 ] 2+ photosensitizer (PS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these issues, metal-organic frameworks (MOFs), bene ting from their porous feature, ordered structure and molecular tunability, have been widely used to mediate photocatalytic CO 2 reduction. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In this eld, Lin et al, 16 incorporated Re(CO) 3 (bpy)Cl (bpy = bipyridine) modules into the UiO-67 framework, achieving a total turnover number (TON) of 10.9 in photocatalytic CO 2 -to-CO conversion. Wang et al achieved a high TON of 450 by using a Co-based zeolitic imidazolate framework as the cocatalyst in the presence of [Ru(bpy) 3 ] 2+ photosensitizer (PS).…”
Section: Introductionmentioning
confidence: 99%
“…15 Recently, perovskite quantum dots were introduced into MOF matrices to synergistically catalyze CO 2 photoreduction. 17,18 For CO 2 reduction, great progress has been achieved with MOFs as low-cost catalysts. However, their performances were seriously hindered by the generally bulky nature with insu cient active sites and lethargic mass/charge transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wu et al reported a novel strategy for enhancing the efficiency of photocatalysis for the CO 2 RR and improving the stability of HPs by encapsulating MAPbI 3 QDs into the porous framework of Fe-porphyrin-based MOF PCN-221(Fe x ). 81 The composite was synthesized following the sequential deposition method (Fig. 8(a)), whereby pristine PCN-221(Fe x ) was first dipped in DMF/ethanol PbI 2 solution, followed by treatment with MAI ethanol solution.…”
Section: Hp Photocatalysis Co 2 Reduction Reactionmentioning
confidence: 99%
“…And, by using ethyl acetate as the solvent for CO 2 , where ethyl acetate could help stabilize the QDs, no degradation was observed after working 12 h [116]. Other composites as CsPbBr 3 /g-C 3 N 4 nanosheet with chemical bonding [168], HP-QDs /metal-organic framework (MOF) with outstanding yield of 1559 μmol/g were also reported [169,170]. Another composite Ag-CsPbBr 3 /CN was fabricated and reported by Zhao et al to degrade 7-aminocephalosporanic acid and exhibited outstanding catalytic activity due to the reduced charge recombination, improved chargeseparation efficiency and light absorption of the whole composite structure [115].…”
Section: Photocatalyst and Photovoltaicmentioning
confidence: 99%